2021
DOI: 10.1002/elps.202000290
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis and molecular modeling of the chiral separation of aromatic amino acids using α/β‐cyclodextrin and 18‐crown‐6

Abstract: In this work, chiral separation of enantiomers of three amino acids was achieved using capillary electrophoresis technique with α‐cyclodextrin (αCD) as a running buffer additive. Only tryptophan has exhibited baseline separation in the presence of αCD, while the enantiomers of the other two amino acids, phenylalanine and tyrosine, were only partially separated. The addition of 18‐crown‐6 (18C6) as a second additive imparted only slight improvement to the separation of all enantiomers. On the other hand, all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The combination of β-CD/18C6 allowed baseline enantio-separation of phenylalanine and tyrosine, which cannot be achieved with only β-CD or 18C6. 77 The synergism of (2-hydroxy-3-N,N,Ntrimethylamino)propyl-γ-CD and CM-β-CD successfully resolved short chiral oligonucleotide in CE. 78 The combination of amino acids-derived CIL with β-CD/HP-β-CD resulted in concentration-dependent promotion in the enantio-separation of dipeptides.…”
Section: ■ Chromatographymentioning
confidence: 99%
“…The combination of β-CD/18C6 allowed baseline enantio-separation of phenylalanine and tyrosine, which cannot be achieved with only β-CD or 18C6. 77 The synergism of (2-hydroxy-3-N,N,Ntrimethylamino)propyl-γ-CD and CM-β-CD successfully resolved short chiral oligonucleotide in CE. 78 The combination of amino acids-derived CIL with β-CD/HP-β-CD resulted in concentration-dependent promotion in the enantio-separation of dipeptides.…”
Section: ■ Chromatographymentioning
confidence: 99%
“…1328 recently, CE enantioseparation involving native CDs was studied by using MM and V analysis, 1334 hybrid ONIOM, 1430 semiempirical calculations, 1431 molecular docking, 1432,1433 and MD simulations. 1280,1331,1431,1434 Methylated CDs have been modelled by using MD simulations with implicit solvent, 1435 semiempirical 1436,1437 and DFT 1437 calculations, and molecular docking. 1436−1438 Even if carboxymethylation of CD can be also performed in a selective way, 1439−1441 some substituted CDs, such as methylated, hydroxypropyl-(HP), CM, and sulfated-(S) β-CD, are used as mixtures of isomers in experimental analyses.…”
Section: Computation-based Modelling Of Enantioseparation Processes A...mentioning
confidence: 99%
“…One of the pioneering studies applying MM to the modelling of CE enantioseparation, and involving native CDs as CSs, was reported in 2002 by Chankvetadze and co-authors . Most recently, CE enantioseparation involving native CDs was studied by using MM and V analysis, hybrid ONIOM, semiempirical calculations, molecular docking, , and MD simulations. ,,, Methylated CDs have been modelled by using MD simulations with implicit solvent, semiempirical , and DFT calculations, and molecular docking. Even if carboxymethylation of CD can be also performed in a selective way, some substituted CDs, such as methylated, hydroxypropyl- (HP), CM, and sulfated- (S) β-CD, are used as mixtures of isomers in experimental analyses. Thus, modelling them as a structurally defined single molecule may provide results which are not reliable for representing the real system, owing to the difficulties in predicting the substitution degree of these CDs.…”
Section: Trends In Enantioselective Recognition In Separation Science...mentioning
confidence: 99%
“…Snapshots of d ‐phenylalanine/α‐CD complex ( A ), and d ‐phenylalanine/α‐CD/18‐crown‐6 ternary ( B ) collected during MD simulation (adapted from Ref. [180] with permission).…”
Section: Molecular Modeling Of Capillary Electrophoresis Enantiosepar...mentioning
confidence: 99%
“…Very recently, Suliman and co‐authors observed that the addition of 18‐crown‐6 can improve CE enantioseparation of phenylalanine and tyrosine with native β‐CD [180], whereas tryptophan enantiomers were not separated with β‐CD alone, and with the dual‐additive system of β‐CD/18‐crown‐6. For the three amino acids, a slight improvement of the enantioseparation was observed by adding the crown ether to α‐CD.…”
Section: Molecular Modeling Of Capillary Electrophoresis Enantiosepar...mentioning
confidence: 99%